2016
DOI: 10.5935/0103-507x.20160029
|View full text |Cite
|
Sign up to set email alerts
|

Drug incompatibilities in the adult intensive care unit of a university hospital

Abstract: ObjectivesThis study sought to identify the physical and chemical incompatibilities among the drugs administered intravenously to patients admitted to an adult intensive care unit. We also aimed to establish pharmaceutical guidelines for administering incompatible drugs.MethodsThis cross-sectional, prospective, and quantitative study was conducted from July to September 2015. Drug incompatibilities were identified based on an analysis of the patient prescriptions available in the hospital online management sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 20 publications
5
27
0
18
Order By: Relevance
“…Risk minimization in coadministration of injectable drugs remains important because polymedication is common practice in various patient groups like cancer patients, transplant patients and intensive care patients (neonatal, paediatric, adult). In recent reports, rates of compatibility varied from 9 to 42 % and of incompatibilities from 15 to 68 % [20][21][22][23][24]. Hospital pharmacists should not only answer questions regarding drug-drug compatibilities, but develop together with physicians and nurses incompatibility-reducing infusion schemes to be used in vulnerable patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…Risk minimization in coadministration of injectable drugs remains important because polymedication is common practice in various patient groups like cancer patients, transplant patients and intensive care patients (neonatal, paediatric, adult). In recent reports, rates of compatibility varied from 9 to 42 % and of incompatibilities from 15 to 68 % [20][21][22][23][24]. Hospital pharmacists should not only answer questions regarding drug-drug compatibilities, but develop together with physicians and nurses incompatibility-reducing infusion schemes to be used in vulnerable patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…These data are similar to the characteristics of patients admitted in other ICUs of the country, where a predominance of male patients and mean age of 53.69 years, 55.8 years, and 60.0 years was observed. [21][22][23] Population aging in the country, resulting in an increased number of individuals with noncommunicable chronic diseases, leads to a higher level of vulnerability of older age groups and increases morbidity and the frequency of hospitalizations of elderly individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous (IV) therapy is commonly used in hospital setting, and it is essential for patients who require urgent medical care or when barriers to oral drug administration exist. [6] The number of IV pharmacotherapies has expanded vastly over the last century and has been associated with a constant need for the concurrent administration of several medications. However, coadministration of IV therapies is sophisticated and usually associated with the risk of incompatibilities between the administered drugs.…”
Section: Drug Incompatibilities: a Dilemma In Clinical Practicementioning
confidence: 99%
“…However, coadministration of IV therapies is sophisticated and usually associated with the risk of incompatibilities between the administered drugs. [1,6] Drug incompatibilities are undesirable interactions that occur during drug preparation or administration process, when two or more drug solutions are mixed in the same syringe, tubing or container. [7] Tissot et al [8] reported that drug incompatibilities account for 14.3% of all intensive care units (ICUs) medication errors.…”
Section: Drug Incompatibilities: a Dilemma In Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation